Carbon quantum dot coated Mn3O4 with enhanced performances for lithium-ion batteries1. Issue 32 (28th August 2015) - Jing, Mingjun; Wang, Jufeng; Hou, Hongshuai; Yang, Yingchang; Zhang, Yan; Pan, Chengchi; Chen, Jun; Zhu, Yirong; Ji, Xiaobo
<x xml:space="preserve">Abstract</x> A C quantum dot coated Mn3O4 composite (Mn3O4/Cdots) has been obtained for the first time by a green alternating voltage electrochemical approach.